Kampong, land and its capacity towards subsistence living / Nur Huzeima Mohd Hussain ... [et al.] - Mohd Hussain, Nur Huzeima; Zakaria, Ahmad Zamil; Ahmad, Suriati; Salleh, Ismail Hafiz (Universiti Teknologi MARA, Perak, 2021)
Kampong is a land that compound by conclusive territory and accommodating people's lives and well-being. As there is anecdotal evidence that people are returning to reoccupying houses and working with the land; this study investigates the land and its capacity for these returnees. The main intention is to identify apparent evidence that land in kampong is accessible and available to be reutilized again. The study presents descriptive information about the attended, productive, and unattended land through site observation and fieldwork measurements. The findings illustrate the capacity of the land to absorb the returnees and allow future subsistence that feeds the demand for food, goods and jobs.